Sistem Pendukung Keputusan Untuk penentuan mustahik (Penerima Zakat) Menggunakan Metode Fuzzy AHP (F-AHP) - Roma Akbar Iswara; Edy Santoso; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Rumah Zakat Malang City is one of the non-governmental organization of zalcat managers who receive and distribute zakat to mustahik. In the process of determining mustahik, the Rumah Zakat Kota Malang checks the data of the recipient to know some criteria that is Child Status, Total Income, Total Dependent and Child Raport Value. The criterion will determine which one gets the most zakat funds. However, the work done by Rumah Zakat in sorting the data is still done manually so it can cause the possibility of not exist in determining which side is more main to receive zakat because of its subjective nature and also need much time selection process that mustahik. Analytical Analytical Process Analytical Hierarchy is one of the better methods in the problem. From the results of calculations from 60 data, obtained the feasibility 91.67% where 5 different data generated with data from the home side of zakat malang. The AHP Fuzzy Method can be used in the determination of mustahik (zakat receiver).